Human Capital Persistence and Development - Rudi Rocha; Claudio Ferraz; Rodrigo R. Soares (Institute for the Study of Labor (IZA), 2015)
This paper examines the role of human capital persistence in explaining long-term development. We exploit variation induced by a state-sponsored settlement policy that attracted a pool of immigrants with higher levels of schooling to particular regions of Brazil in the late 19th and early 20th century. We show that municipalities that received settlements experienced increases in schooling that persisted over time. One century after the policy, localities that received state-sponsored settlements had higher levels of schooling and income per capita. We provide evidence that long-run effects were driven by persistently higher supply and use of educational inputs and shifts in the structure of occupations towards skill-intensive sectors.
Keywords: O15; O18; N36; 330; human capital; education; immigration; development